2000
DOI: 10.1074/jbc.m006229200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Properties of the Rat AA4 Antigen, a C-type Lectin-like Receptor with Structural Homology to Thrombomodulin

Abstract: The murine fetal stem cell marker AA4 has recently been cloned and is known to be the homolog of the human phagocytic C1q receptor involved in host defense. We herein report the molecular cloning and the cellular expression pattern of the rat AA4 antigen. Modular architecture analysis indicated that the rat AA4 is a member of C-type lectin-like family and, interestingly, displays similar domain composition and organization to thrombomodulin. Northern blot and reverse transcriptase-polymerase chain reaction ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 45 publications
1
52
0
1
Order By: Relevance
“…2/2 mice of both genders have an increased infarct volume when compared with WT-mice at 72 h after induction of transient focal cerebral ischemia BecauseoftheinvolvementascribedtoCD93inphagocytoticprocesses and angiogenesis, we analyzed infarct volumes in a second experimental stroke model, which does not cause infarction (i.e., pannecrosis) but rather selective neuronal cell death with a profound neuroinflammatory response (36,37). In contrast to the findings after 60 min MCAO (Fig.…”
Section: Cd93mentioning
confidence: 79%
See 1 more Smart Citation
“…2/2 mice of both genders have an increased infarct volume when compared with WT-mice at 72 h after induction of transient focal cerebral ischemia BecauseoftheinvolvementascribedtoCD93inphagocytoticprocesses and angiogenesis, we analyzed infarct volumes in a second experimental stroke model, which does not cause infarction (i.e., pannecrosis) but rather selective neuronal cell death with a profound neuroinflammatory response (36,37). In contrast to the findings after 60 min MCAO (Fig.…”
Section: Cd93mentioning
confidence: 79%
“…The molecular structure of CD93 is reminiscent of thrombomodulin, a receptor for thrombin that is recognized as a major natural anticoagulant mainly expressed on endothelial cells and platelets (31,36). CD93 and thrombomodulin seem to be derived from a common ancestor (31).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the NH 2 -terminal lectin-like domain of thrombomodulin is structurally similar to human phagocytic C1q receptor, which acts as an adhesion molecule for innate immune host defense. The evidence is also suggesting that the lectin-like domain of thrombomodulin may have an important role for cell-cell interaction (37,38). Thus, we strongly put forth the hypothesis that thrombomodulin may be an essential antimetastatic factor in ␤-cell tumors, acting as a counter-ligand or associate molecule for neural cell adhesion molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting analysis revealed CD93 to be a 126-kDa protein in reducing conditions and a 90 to 100-kDa protein in non-reducing conditions (13,30,38). Glycosylation studies showed human CD93 to be a heavily O-glycosylated type I transmembrane protein consisting of unique C-type lectin domains displaying a 68% homology to rat or mouse AA4 antigen (6,7).…”
mentioning
confidence: 99%